Menstruation hygiene management among secondary school students of Chitwan, Nepal, Pre-post study design. - Khanal, Gayatri (2021)
SUMMARY: The study entitled "Menstruation Hygiene management among secondary school students of Chitwan, Nepal- Pre -Post Study Design" was conducted as pre and posttest study design. The overall goal of this study was to improve the health of school going adolescent by fostering good knowledge and promoting a healthy practices to manage menstruation for better health. Specifically, in the present study, menstruation hygiene management (MHM) knowledge, practices, prevailing cultural restrictions, school absenteeism due to menstruation and the effectiveness of educational interventions among adolescent girls in Chitwan District was examined. This study was part of NHRC research grant, as it will run by the provincial research grants fiscal year 2077-2078". Thus, academic studies will be conducted using tools like self-administered questionnaire, and observational checklist. In this study, data was entered using Epi-data 3.1 software and analyzed using SPSS 16. The statistical analysis carried out was descriptive, bivariate (chi-square test), multivariate analysis (Binary logistic regression) and pair wise t-test. Ethical approval was obtained from Nepal Health Research Council on April 7, 2021. Findings were looked for 1) the knowledge on menstruation hygiene management 2) Existing practice on menstruation hygiene management 3) Cultural restriction faced by adolescent girls during menstruation cycle. 4) Effectiveness of educational intervention on menstruation hygiene management. More than half (65.7%) of the respondents has more than one siblings in their home. More than three quarter (87.0 %) of the girls were never participated in MHM program. 43.6% girls felt embarrassed when they had their first menstruation. 21.3% girls had never ever used sanitary pad in their lifetime. Nearly, 4.5% had never washed their genetilia during menstruation. More than half (68%) of the respondents took the same amount of rest as in normal days. More than one third of the girls (38.7%) disposed their pad in municipality garbage . 18.7% of the girls never washed hands after changing pad. 61.4% girls missed their classes/ schools day due to menstruation. Most of the respondents (93.8%) had experienced at least a single cultural restriction in their life during menstruation. Every school had a separate girl's toilet but only 61.5% and 65.3% of the toilets had functioning lock and bin availability in the toilet premises respectively. Level of knowledge rank was in posttest was statistically significantly higher than level of knowledge rank in pretest (z= , p=<0.001) This result clearly explained that the education on menstruation hygiene to the secondary school girls is one of the good strategy to enhance level of knowledge on menstruation hygiene. There is significant association between age group (p<0.001), ethnicity (p=0.033), Types of school (p=), Father Education (p=0.003), mother education (p=0.005) and mother occupation (p<0.001) The findings of this study is shared with concern stakeholders (Nepal Health Research Council, District Educational office Chitwan, Concern person of Municipality and the schools of Chitwan). Publication of the research result will be done in a reputed journal later. The result of this will developed strong evidence on how we can protect the enhance the health and wellbeing of future adolescent and also it can draw the attention of the policy makers to make policy in a way that they could involve all the integral components (MHM ) to achieve healthy lives and promote well-being for school going adolescent.